Abstract Art in Belgium / Flanders : Origin and Fundamentals. - Meewis, Wim; Ministerie van de Vlaamse Gemeenschap; Itami City Museum of Art, Itami (Brussel : Gemeentekrediet, 1990)
Servranckx, Victor ; Flouquet, Pierre-Louis ; Joostens, Paul ; Seuphor, Michel ; Peeters, Jozef ; Maes, Karel ; Kiemeneij, Jan ; Donas, Marthe ; Baugniet, Marcel-Louis ; Gailliard, Jean-Jacques ; Closon, Henri-Jean ; Delhez, Victor ; Ongenae, Jozef ; Delahaut, Jo ; Bertrand, Gaston ; Peire, Luc ; Leblanc, Walter ; Verheyen, Jef ; Van Severen, Dan ; Cortier, Amédée ; Swimberghe, Gilbert ; Van Doorslaer, Etienne ; De Sauter, Willy
Abstract Art in Belgium / Flanders : Origin and Fundamentals, Itami City Museum of Art, Itami, 7 October 1990 - 18 November 1990. This exhibition is organized by the Commissariat-General for the International Co-operation of the Flemish Community and the Gemeentekrediet of Belgium on the occasion of the Belgium - Flanders - Hasselt - Week in the city of Itami.
boek
Keywords: België; Vlaanderen